2011
DOI: 10.1021/jm200694q
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Fosmidomycin Derivatives against the Antimalarial Drug Target IspC (Dxr)

Abstract: Reverse hydroxamate-based inhibitors of IspC, a key enzyme of the non-mevalonate pathway of isoprenoid biosynthesis and a validated antimalarial target, were synthesized and biologically evaluated. The binding mode of one derivative in complex with EcIspC and a divalent metal ion was clarified by X-ray analysis. Pilot experiments have demonstrated in vivo potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 34 publications
(25 reference statements)
1
59
1
Order By: Relevance
“…Kuntz et al (2005) synthesized two phosphonohydroxamic acids which showed inhibitory activity towards DXR as well as antibacterial activity against E. coli in vitro. Indeed, Behrendt et al (2011) very recently reported the antiplasmodial activity of IspC/Dxr inhibitors.…”
Section: The Mep Pathway As a Drug Targetmentioning
confidence: 99%
“…Kuntz et al (2005) synthesized two phosphonohydroxamic acids which showed inhibitory activity towards DXR as well as antibacterial activity against E. coli in vitro. Indeed, Behrendt et al (2011) very recently reported the antiplasmodial activity of IspC/Dxr inhibitors.…”
Section: The Mep Pathway As a Drug Targetmentioning
confidence: 99%
“…Reverse hydroxamate-based inhibitor for IspC enzyme was evaluated by Behrendt et al (2011) [37]. Fosmidomycin has been proven to be efficient in the treatment of P. falciparum malaria by inhibiting 1-deoxy-D-xylulose-5-phosphate reductoisomerase (DXR), an enzyme of the nonmevalonate pathway, which is absent in humans (Figure 4).…”
Section: Antimalarial Compounds Against Isoprenoid Biosynthetic Pamentioning
confidence: 99%
“…15,17 Extensive crystallographic studies on DXRs from different species have provided the structural framework needed to understand the binding of these inhibitors, 10,[18][19][20][21] as well as their α-aryl-substituted analogues. 7,22,23 Despite the lack of biological activity of fosmidomycin itself against M. tuberculosis, the well-conserved nature of the active site of DXR, 21 combined with the anti-parasite activity of some DXR inhibitors, led us to believe that our medicinal chemistry effort based on MtDXR would produce interesting compounds for use against other pathogens where the MEP pathway is essential. It also seemed possible that some fosmidomycin analogues would in fact be active against M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%